Afterlives Scandinavian Classics as Comic Art Adaptation - STORSKOG, CAMILLA CARITA (Kriterium, 2023)
Afterlives is a study of how Scandinavian classics have been reinterpreted as comics. Literary scholar Camilla Storskog investigates how storytellers like H.C. Andersen, Henrik Ibsen, Karen Blixen, and Ingmar Bergman have crossed and recrossed media boundaries in the hands of international comics creators such as Bo Vilson, Guido Crepax, Cinzia Ghigliano, Peter Madsen, and Pierre Duba. Comics have long been neglected in the field of adaptation studies. By focusing on the aesthetic, technical, and narrative qualities of the comics medium, Afterlives presents a theoretical and methodological framework for the analysis of intersemiotic translation. The narrative complexities of comics and the connections between adaptation and adapted text, new times and changing contexts are explored in an inspired account of visual storytelling.